AN ANALYSIS ON KRI IMPROVEMENT PROJECT IN INDONESIAN NAVAL MAIN BASE NO. V SURABAYA FASHARKAN (NAVY’S BATTLESHIPS MAINTENANCE AND REPAIRING FACILITIES USING FUZZY FMEA METHOD - Eko Krisdiono; I Nengah Putra A; I Made Jiwa Astika; Bambang Suharjo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The FMEA method is a tool used to identify the consequences or consequences of a system or process failure and reduce or eliminate failure. In determining risk factors and system improvement priorities, traditional FMEA still has weaknesses, where FMEA traditionally places severity factors, occurrence, and detection at the same level of importance, even though in reality different levels of importance and the importance of FMEA assessment teams are ignored. In this study, the fuzzy method is integrated into FMEA where the severity factor, occurrence, and detection are assessed in linguistic form. In this fuzzy method, the weight of the interests of the FMEA assessment team is taken into account to do ranking and repair priorities. The application of Fuzzy methods to FMEA to determine significant risk factors and prioritizing improvements from various alternatives chosen for the process of repairing KRI in Surabaya Lantamal V, so that it is expected that the application of this method can improve the operational performance of Fasharkan to eliminate or reduce the risks that occur in the repair process ships in the eastern region of the fleet. Keywords: Risk Management, Failure Modes and Effect Analysis (FMEA), Fuzzy Method